Contemporary applications of wavefront aberrometry in ophthalmology practice - Moćko, Lucyna; Zając, Marek; Roszkowska, Anna; Węglarz, Beata; Milka, Michał; Dobrowolski, Dariusz; Wylęgała, Edward (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
The aim of the article is to present and summarize the current knowledge of wavefront aberrations, methods and applications of aberrations measurement. Ideal optical system is stygmatic, which means that object point is imaged by optical system into the image point without deformation. Optical system of the eye is not ideal, it has aberrations. Aberrations limitate and determine visual quality. Wavefront aberrometers measure manochromatic low and high order aberrations. Wavefront aberrations are described by Zernike polinomials. More important wavefront sensor types are described in the article. In their practice authors use KR1W Topcon aberrometer. Authors also present difficulties in taking aberrometric measurements. In recent years quality of vision becomes the point of interest for vision scientists. Correction of high order aberrations is the future of optics.